Reset integral control for improved settling of PID-based motion systems with friction - Beerens, R.; Bisoffi, A.; Zaccarian, L.; Heemels, W.P.M.H.; Nijmeijer, H.; van de Wouw, N. (Automatica (Oxford), 2019)
We present a reset control approach to improve the transient performance of a PID-controlled motion system subject to Coulomb and viscous friction. A reset integrator is applied to circumvent the depletion and refilling process of a linear integrator when the solution overshoots the setpoint, thereby significantly reducing the settling time. Robustness for unknown static friction levels is obtained. The closed-loop system is formulated through a hybrid systems framework, within which stability is proven using a discontinuous Lyapunov-like function and a meagre-limsup invariance argument. The working principle of the proposed reset controller is analyzed in an experimental benchmark study of an industrial high-precision positioning machine.